Optimization Of Carboxymethyl Cellulose (CMC) Synthesis In Production Of Hydrogel From Ananas comosus L. Leaves - Ardelia Devina; Roni Maryana; Mirad Fahri; Anggi Khairina Hanum Hasibuan; Tasrikin Agustianto (JOURNAL SAINS STUDENT RESEARCH, 2025)
Cellulose and its derivatives are important industrial raw materials because of their abundance, biodegradable properties, environmentally friendly, and have good mechanical and thermal properties. This study aims to determine the synthesis process and characteristics of carboxymethyl cellulose (CMC) in the manufacture of hydrogels from pineapple leaf waste. The stages of the CMC synthesis process from pineapple leaves are carried out through the process of delignification, bleaching, alkalization and carboxymethylation. Cellulose modification was done by alkalization method using 30% NaOH and variation of temperature and time on carboxymethylation with monocloroacetic acid (MCA) in 2-propanol solvent. In the manufacture of CMC hydrogel was made by using calcium chloride (CaCl2) as a crosslink agent. The results showed that CMC from pineapple leaf waste had good quality with pH 6,0-7,5 and degree of substitution values ranging from 0,4-1,2. Carboxymethyl cellulose and hydrogel produced showed the presence of O-H, C-H and C=O functional groups. The presence of ATR-IR peak 1053-1104 cm⁻¹ in the bleached product confirmed the presence of β-(1,4)-glycosidic bond of pure cellulose, while the peak at 1500-1700 cm⁻¹ of the modified cellulose product confirmed the carbonyl group of carboxymethyl cellulose (CMC).